Glucagon stimulates exocytosis in mouse and rat pancreatic alpha-cells by binding to glucagon receptors. - Ma, X; Zhang, Y; Gromada, J; Sewing, S; Berggren, P; Buschard, K; Salehi, A; Vikman, J; Rorsman, P; Eliasson, L (2005)
Glucagon, secreted by the pancreatic alpha-cells, stimulates insulin secretion from neighboring beta-cells by cAMP- and protein kinase A (PKA)-dependent mechanisms, but it is not known whether glucagon also modulates its own secretion. We have addressed this issue by combining recordings of membrane capacitance (to monitor exocytosis) in individual alpha-cells with biochemical assays of glucagon secretion and cAMP content in intact pancreatic islets, as well as analyses of glucagon receptor expression in pure alpha-cell fractions by RT-PCR. Glucagon stimulated cAMP generation and exocytosis dose dependently with an EC50 of 1.6-1.7 nm. The stimulation of both parameters plateaued at concentrations beyond 10 nm of glucagon where a more than 3-fold enhancement was observed. The actions of glucagon were unaffected by the GLP-1 receptor antagonist exendin-(9-39) but abolished by des-His1-[Glu9]-glucagon-amide, a specific blocker of the glucagon receptor. The effects of glucagon on alpha-cell exocytosis were mimicked by forskolin and the stimulatory actions of glucagon and forskolin on exocytosis were both reproduced by intracellular application of 0.1 mm cAMP. cAMP-potentiated exocytosis involved both PKA-dependent and -independent (resistant to Rp-cAMPS, an Rp-isomer of cAMP) mechanisms. The presence of the cAMP-binding protein cAMP-guanidine nucleotide exchange factor II in alpha-cells was documented by a combination of immunocytochemistry and RT-PCR and 8-(4-chloro-phenylthio)-2'-O-methyl-cAMP, a cAMP-guanidine nucleotide exchange factor II-selective agonist, mimicked the effect of cAMP and augmented rapid exocytosis in a PKA-independent manner. We conclude that glucagon released from the alpha-cells, in addition to its well-documented systemic effects and paracrine actions within the islet, also represents an autocrine regulator of alpha-cell function.